Modis images for agrometeorological monitoring of coffee areas - Volpato, Margarete Marin Lordelo; Vieira, Tatiana Grossi Chquiloff; Alves, Helena Maria Ramos; Santos, Walbert Júnior Reis (Coffee Science - ISSN 1984-3909, 2013)
Agrometeorological monitoring of coffee lands has conventionally been performed in the field using data from land-based meteorological stations and field surveys to observe crop conditions. More recent studies use satellite images, which assess large areas at lower costs. The Moderate Resolution Imaging Spectroradiometer (MODIS) sensor of the Earth satellite provides free images with high temporal resolution and vegetation specific products, such as the MOD13, which provides the Normalized Difference Vegetation Index (NDVI) processed in advanced. The objective of this study was to evaluate the relation between the NDVI spectral vegetation index and the meteorological and water balance variables of coffee lands of the south of Minas Gerais in order to obtain statistical models of this relationship. The study area is located in the municipality of Três Pontas, Minas Gerais, Brazil. The statistical models obtained demonstrate a significant negative correlation between the NDVI and water deficit. NDVI values under 70% may represent a water deficit in the coffee plants. The models developed in this study could be used in the agrometeorological monitoring of coffee lands in the south of Minas Gerais.